BRCA mutation characteristics in a series of index cases of breast cancer selected independent of family history. Issue 5 (22nd June 2019) - Bisgin, Atil; Boga, Ibrahim; Yalav, Orcun; Sonmezler, Ozge; Tug Bozdogan, Sevcan
Abstract: Certain genetic predisposition factors, such as BRCA1 and BRCA2 mutations play a pivotal role in familial breast cancer development in both males and females. Due to this, the importance and necessity of genetic screening to identify mutations affecting the population is paramount. Undergoing genetic screenings allows for a more knowledgeable risk assessment for the patients and their care providers. The aim of this study was to evaluate the prevalence of BRCA1/BRCA2 mutated genes in the Turkish population among unselected patients. To identify the molecular markers, we utilized a gene panel analysis consisting of BRCA1 and BRCA2 genes, with a next generation sequencing platform (MiSeq System, Illumina). Sequencing was performed using leukocyte DNA from breast cancer patients. In‐silico analysis for novel mutations was carried out using SIFT, PolyPhen2 and MutationTaster. BRCA1 and BRCA2 pathogenic variants were identified in 18 of 129 (14%) patients among the study population; of those 18 patients, seven (39%) were found in the BRCA1 gene and 11 (61%) in the BRCA2 gene. Ten of the eleven BRCA2 variants (90%) were novel mutations. Four of ten (40%) of the novel mutations were determined to be deleterious and six out of ten (60%) were identified as single nucleotide variations. Clinically significant mutations of the BRCA1/BRCA2 genes are related to an increased susceptibility for breast cancer. There is however, little known about BRCA mutations amongst the general population. Thus, it is important that patients are able to undergo genetic screenings and counseling. This also allows for greater care from health care providers and can only facilitate disease prevention which in turn can lead to a decreased cancer morbidity rate.